RELATIONSHIP BETWEEN PARENTS' ATTENTION AND INTEREST IN LEARNING ON STUDENTS' PAI LEARNING OUTCOMES IN THE FIRST MIDDLE SCHOOL OF DARUSSALAM MEDAN LABUHAN - Loka, Lola Retia; Hidayat, Rahmat; Suyani, Erni (Universitas Dharmawangsa, 2023)
Parental attention has a great relationship with children's learning activities. With the attention of parents, children will be more active and more enthusiastic in learning. The background of this research problem is that ideally a child can have a good Islamic education learning achievement if the child gets high or sufficient attention from his parents. Because, a child, especially in the period of development, certainly needs a trusted figure who can guide, direct and be a role model.This study aims to determine: (1) the quality of parental attention to children's learning in the field of Islamic education at Junior high school Darussalam Medan Labuhan, (2) student interest in learning in the field of Islamic education at Junior high school Darussalam Medan Labuhan, and (3) the relationship between parental attention and interest learning on student achievement in the field of Islamic Studies at Junior high school Darussalam Medan Labuhan.This research is a quantitative research. The analysis used in this research is correlation. This technique is used to connect the measurement results between two different variables in order to determine and obtain information about the degree of relationship that occurs between the two variables. The correlation technique used in this study is serial correlation.